Growth of GaN on monolayer hexagonal boron nitride by chemical vapor deposition for ultraviolet photodetectors. (27th October 2020) - Zhu, Wenhui; Si, Jiawei; Zhang, Lei; Li, Tao; Song, Wenqing; Zhou, Yuting; Yu, Jiahao; Chen, Rui; Feng, Yexin; Wang, Liancheng
Abstract: Chemical vapor deposition (CVD) technology is a simple and flexible method used to prepare high-quality crystalline materials. Traditional CVD technology, based on pre-deposited thin catalyst metal, usually produces nanostructures instead of continuous films. In this work, a continuous GaN film on a monolayer boron nitride (h-BN) insertion layer is demonstrated using CVD technology. The experimental results and theoretical calculations indicate that abundant GaN nanocrystallites are firstly formed at the edges or grain boundaries of the monolayer h-BN by quasi-van der Waals epitaxy. Then, the vapor-solid mechanism will control further growth of the GaN nanocrystallites, causing them to merge into a continuous GaN film. Meanwhile, the CVD-grown GaN ultraviolet detector exhibits a relatively high responsivity with a value of 0.57 A W −1 at 2 V. In this paper, a simple low-cost CVD method is proposed for preparing continuous films on two-dimensional materials for electronic and optoelectronic devices.